2019
DOI: 10.1039/c9ob00085b
|View full text |Cite
|
Sign up to set email alerts
|

Salts accelerate the switching kinetics of a cyclobis(paraquat-p-phenylene) [2]rotaxane

Abstract: The switching speed of a bistable [2]rotaxane upon oxidation is found to be increased in the presence of added salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The UV/Vis/NIR dilution method (Supporting Information) was used to determine (Table ) the binding constant ( K a ) and the Gibbs free energy (Δ G °) associated with the formation of 10 ⊂CBPQT 4+ in MeCN at 298 K, whereas K a and Δ G ° values for the formation of 11 – 13 ⊂CBPQT 4+ were taken from the literature . Since the binding between CBPQT 4+ and the OP unit is very low ( K a =16 m −1 ), it is clear that the translational isomer 1 ⋅OP 4+ will not be present in 1 4+ to any significant extent (<1 %). Assuming that the relative populations between 1 ⋅MPTTF 4+ , 1 ⋅HQ 4+ , and 1 ⋅TTF 4+ are related to the free energies listed in Table , a calculated isomer distribution of 6 % 1 ⋅TTF 4+ , 86 % 1 ⋅MPTTF 4+ , and 8 % 1 ⋅HQ 4+ can be obtained .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The UV/Vis/NIR dilution method (Supporting Information) was used to determine (Table ) the binding constant ( K a ) and the Gibbs free energy (Δ G °) associated with the formation of 10 ⊂CBPQT 4+ in MeCN at 298 K, whereas K a and Δ G ° values for the formation of 11 – 13 ⊂CBPQT 4+ were taken from the literature . Since the binding between CBPQT 4+ and the OP unit is very low ( K a =16 m −1 ), it is clear that the translational isomer 1 ⋅OP 4+ will not be present in 1 4+ to any significant extent (<1 %). Assuming that the relative populations between 1 ⋅MPTTF 4+ , 1 ⋅HQ 4+ , and 1 ⋅TTF 4+ are related to the free energies listed in Table , a calculated isomer distribution of 6 % 1 ⋅TTF 4+ , 86 % 1 ⋅MPTTF 4+ , and 8 % 1 ⋅HQ 4+ can be obtained .…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we describe the synthesis and characterization of a tetra‐stable [2]rotaxane 1 ⋅4PF 6 (Figure ) in which the dumbbell contains four potential stations for CBPQT 4+ , namely an oxyphenylene (OP), a TTF, a monopyrrolo‐TTF (MPTTF), and a HQ station. The TTF and the MPTTF stations are located in the middle of the dumbbell and are connected by a triethylene glycol (TEG) chain in such a way that the pyrrole moiety of the MPTTF unit points toward the TTF station .…”
Section: Introductionmentioning
confidence: 99%
“…These interlocked compounds have been used extensively and successfully to create artificial molecular machines (AMMs) 10 in an effort to mimic both biological processes (biomimetic 11 ), such as the controlled molecular motion taking place in ATP-synthase 12,13 or kinesin's ability to walk along the microtubule filament, 14 and macroscopic processes (technomimetic 11 ), such as pumps, 15–19 cars 20 and elevators. 21 These designs often rely on controlling 15,22–24 the mechanisms of stimuli-driven motion, and thus motivate studies of kinetics 25–29 and the underlying energy landscapes. 30,31 We do this here by measuring the impact of double oxidation on the barrier to the motion of a mobile ring (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…38 Lately, the dependence of the shuttling kinetics of an electrochemically switchable CBPQT 4+ -rotaxane on the electrolyte concentration was investigated by Jeppesen and co-workers. 60 For electrochemical experiments, supporting electrolytes are frequently required in high concentrations to increase solution conductivity. It was found that tetraalkylammonium salts (R 4 N + X À ) in general lead to an increased switching rate, whereas the size of the R 4 N + cation has no signicant effect on wheel shuttling.…”
Section: Kinetics Of Redox-controlled Molecular Shuttlesmentioning
confidence: 99%